Assessment of water quality in coal mines: A quantitative approach - Yadav H.L.; Jamal A. (My University, 2025)
The water quality in mines is a major issue of concern globally. Coal mines in India have relating good quality of water with only a few exceptions. There are more than 36 parameters to explain the quality of water in a particular water body. There may be one index value which will decide the quality of water in quantitative terms. In this paper, an attempt has been made to give an index of water collected from coal mines of India with the help of methods of water quality index available. The water samples collected from mines were analyzed for 13 physicochemical parameters likes, pH, turbidity, hardness, magnesium, chloride, calcium, nitrate, sulphate, total dissolved solids, electrical conductivity, iron, DO and BOD. The water quality index of these mine water samples varies from 26.79 to 19719.84.The higher value of WQI has been found very inferior quality due to the presence of iron, nitrate, hardness and sulphate, in the sump water sample. The obtained results from laboratory analysis can be used to propose suitable treatment process for using the water for different purposes. © RASĀYAN. All rights reserved.